Permainan Tradisional Edukatif Ã¢â‚¬Å“MpaÃƒÂ¡ NcimiÃ¢â‚¬Â Sebagai Metode Untuk Meningkatkan Kemampuan Motorik Dan Perilaku Sosial Anak - Hardiningsih, Sri; Akbar, Muhammad Rijalul; Nurrahmah, Nurrahmah (Jurnal Golden Age, 2020)
In stimulating a child's motor development, both fine and gross motor skills can use games. Games in learning for children can also foster pleasure, happiness and develop social behavior. Research on the "Educational Traditional Game" MpaÃƒÂ¡ Ncimi "as a Method for Improving Motor Skills and Social Behavior for Children in An-Nur Kindergarten PGRI Bima City" aims to: (1) Grow and appreciate again traditional games in general, especially in the City of Bima ; (2) Creating a learning method for teachers; (3) Developing motor skills and social behavior in early childhood. This research uses a descriptive qualitative approach. Data collection techniques used are, observation, interview and documentation. The conclusion of this study is that traditional educational games that are applied can provide stimulus or stimulation for motor skills and social behavior of children.